Diffuse Cutaneous Angiosarcoma in the Scalp and Face Demonstrated on FDG PET/CT Imaging. (September 2021) - Xiao, Liu; Zhang, Wenjie; Li, Lin
Abstract : Abstract: Diffuse cutaneous angiosarcomas are rare. Herein, we reported FDG PET/CT findings of cutaneous angiosarcoma in a 59-year-old man. FDG PET/CT imaging was performed for staging, showing diffuse intense FDG uptake with an SUVmax of 19 in the scalp and face. Chemotherapy was recommended for this patient because surgery and radiotherapy were not appropriate due to the widespread skin involvement. Our case suggests that cutaneous angiosarcoma can present with diffuse skin involvement, and FDG PET/CT plays an important role in determining the treatment plan to avoid unnecessary surgery and radiotherapy.